The Sweetpotato Knowledge Portal: The virtual resource for everything about sweetpotato - Bukania, C. (International Potato Center, 2015)
Since late 2014, work has been ongoing to transform the Sweetpotato Knowledge Portal into a user-friendly, single access point for discovery, acquisition and sharing of information about sweetpotato research and activities. This flyer is a summary of the process of upgrading the portal as at July 2015, and the future plans.